2002
DOI: 10.1097/00125817-200207000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cystic fibrosis carrier screening programs according to genetic screening criteria

Abstract: Genetic screening programs should meet certain criteria before they can be introduced into the community. The aim of this study was to discuss pilot studies for cystic fibrosis (CF) carrier screening before and during pregnancy in the light of important genetic screening criteria. Overall, CF carrier screening meets the prerequisites that justify screening. However, more specific criteria for the development of screening programs were not always taken into consideration. Most project leaders concentrated on up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
30
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 48 publications
0
30
1
Order By: Relevance
“…Nevertheless, we conclude that an offer of combined preconceptional ancestry-based CF and HbPs carrier couple screening does not cause major negative psychological harm, which is one of the prerequisites of offering genetic screening according to the genetic screening criteria. 46 With regard to knowledge and understanding of the testresults, the results of the present study showed no major difference from those of previous studies either. Knowledge improved significantly from before to just after the pretest consultation.…”
Section: Discussioncontrasting
confidence: 59%
“…Nevertheless, we conclude that an offer of combined preconceptional ancestry-based CF and HbPs carrier couple screening does not cause major negative psychological harm, which is one of the prerequisites of offering genetic screening according to the genetic screening criteria. 46 With regard to knowledge and understanding of the testresults, the results of the present study showed no major difference from those of previous studies either. Knowledge improved significantly from before to just after the pretest consultation.…”
Section: Discussioncontrasting
confidence: 59%
“…Studies of other carrier screening programs, such as for CF, have suggested that teaching new and abstract concepts in genetics is difficult, particularly when existing public knowledge is limited. 18,19 Contrary to these studies, the school community knowledge in the Melbourne TSD carrier screening program was high, even before education, probably because of a continuously increasing awareness in this population. Although knowledge is an important outcome of an educational intervention, it is clear from the study described here that psychosocial and behavioral outcomes are equally, if not more, relevant in the decision-making process because they showed significant associations with student decisions.…”
Section: Discussionmentioning
confidence: 77%
“…The majority of studies reported little evidence of long-term psychological harm, with the provision of counseling. This is supported by Henneman et al, 98 who reported that the potential psychological harms associated with population-based CF carrier screening are insufficient to warrant the refusal to offer carrier screening to the general population in the Netherlands.…”
Section: Discussionmentioning
confidence: 85%